Third Annual Fresno County Young Lawyers Hopper Luncheon with Justice Allen Broussard - Watkins, Howard::::::::: (1984)
Debra Kazanjian, Justice Allen Broussard, Fresno County Young Lawyers Association President Herbert Levy, Justice Donald Franson Luncheon at Golden State Plaza ballroom: ceramic artwork on wall